IMPLEMENTASI PROGRAM KELURAHAN SIAGA BENCANA (KSB) DI KECAMATAN NGALIYAN KOTA SEMARANG - Zahrah, Zahirah; Hidayat, Zainal (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Village Disaster Preparedness (Kelurahan Siaga Bencana) is a village that has ability to recognize threats in their area. It is also able to organize community resources to reduce vulnerability and to increase capacity of their community in order to reduce disaster risk. This ability is embodied in planning the efforts of prevention, preparedness, disaster risk reduction and increased capacity for post-emergency recovery. The purpose of this study is to describe how the implementation of the Village Disaster Preparedness Program in Ngaliyan, Semarang and to determine the supporting and resisting factors of Village Disaster Preparedness Program in Ngaliyan, Semarang. This research is a descriptive study by using a qualitative approach.The result shows that in its practical, there are some situations that resisting the implementation of program. This is caused by the weakness of the human resources, funds resource and facilities resources factors. The recommendations which can be given is related to human resources that can be improved in quantity and quality, financial resources in order to provide a special estimation to the implementation and improvement of the quality in facilities and infrastructure on the implementation of the program.